Kehidupan Sosial-Budaya Masyarakat Tionghoa di Batavia 1900an-1930an - Wildan Sena Utama (Universitas Gadjah Mada, 2012)
This paper discusses the everyday life of the Tionghoa society in Batavia in the frst forty years of the twentieth century. The everyday life of the Tionghoa society in Batavia has so far been left unexplored. Existing studies on this particular group of people have mostly focused on the economic and political dimensions, for example the business activities of the Tionghoa society and the policy of discrimination for and against them made by successive governments in Indonesia. This paper shows that the social dimension can be an effective approach to study the many issues of the topic.